Mathematics Teaching Using Generative Learning Model with Character Building Content Aided by Interactive Learning Media - Rahayu, Rita; Masrukhan, Masrukhan; Sugianto, Sugianto (Universitas Negeri Semarang, 2019)
This research is aimed at generating a Mathematics learning instrument using generative learning model with character building content aided by interactive learning media from the topic of Geometry for VIII graders, which is valid, effective for conceptual understanding, and descriptive in terms of learning instrument development characteristics. It is a developmental research using the 4-D model of Thiagarajan, which consists of defining, designing, developing, and disseminating. This research managed to finish three of those four stages. The learning instruments developed are the Syllabus, the Interactive Learning Media (Media Pembelajaran Interaktif/MPI), Plan for Teaching Execution (Rencana Pelaksanaan Pembelajaran/RPP), Students’ Worksheet (Lembar Kerja Peserta Didik/LKPD), and Learning Potential Test (Tes Prestasi Belajar TPB) Data collection was carried out using testing, documentation, and observational methods.Results of data analysis show lead to the conclusion that validation for Syllabus, MPI, RPP, LKPD, and TPB indicate fulfillment of all validity criteria. Effective learning for concept understanding skills is marked with (1) classical learning completion, in which students taught using the generative learning model with character building content aided by interactive media learning are 80% successful, or equals to 75 minimum score, (2) students involvement in learning that positively affects their achievement, and (3) better achievement attained by students taught using the generative learning model with character building content aided by interactive media learning, compared to conventional learning model. The characteristics developed for Mathematics teaching using the generative learning model with character building content aided by interactive media learning are aimed at improving students’ achievement in terms of concept understanding of Geometry, involving learning stages of generative learning model syntax, which consists of (1) introduction or exploration, (2) focusing, (3) challenge, and (4) application.